Math, asked by naveenchandprajapati, 1 year ago

Solution of x+b/a-b=x-b/a+b is

Answers

Answered by afabdava
2

Answer:

-a.

Step-by-step explanation:

Given x+b/a-b = x-b/a+b can be written as

          (x+b)(a+b) = (x-b)(a-b)

         xa + xb + ab + b^2 = xa - bx - ba + b^2

         xa + xb + ab + b^2 - xa + bx + ba - b^2

         2xb + 2ab = 0

          2b(x + a) = 0

          x + a = 0

         x = -a.

        

Read more on Brainly.in - https://brainly.in/question/1835547#readmore

Similar questions